Психолінгвальні закономірності відтворення художнього тексту в перекладі (на матеріалі англійської та української мов) - Засєкін, Сергій Васильович; Zasiekin, S.V. (Харків : Харківський національний університет імені В.Н. Каразіна, 2020)
Дисертацію присвячено вивченню психолінгвальних закономірностей як нетипових рис у перекладі художніх творів з англійської на українську. Дослідження ґрунтується на засадах теорії релевантності щодо розмежування мовних одиниць – носіїв процедурного та концептуального значення. Аналіз паралельного англо-українського корпусу та зіставного українського корпусу художніх прозових творів на основі комп’ютерних інструментів психолінгвістичного та статистичного аналізу засвідчив систематичний прояв, відповідно: Д-закономірностей ускладнення, нормалізації, спрощення, вирівнювання, експліцитації, імпліцитації, дераціоналізації; Ц-закономірностей спрощення, експліцитації, вирівнювання, імпліцитації, нормалізації, ускладнення, дераціоналізації.
Psycholinguistic Regularities of Reproducing Literary Texts in Translation (Based on the English and Ukrainian Languages)
Zasiekin S.V. Psycholinguistic Regularities of Reproducing Literary Texts in Translation (Based on the English and Ukrainian Languages). Manuscript. Dissertation for a Doctoral Degree in Philology, Speciality 10.02.16 – Translation Studies / Lesya Ukrainka Eastern European National University. Ministry of Education and Science of Ukraine; V. N. Karazin Kharkiv National University, Ministry of Education and Science of Ukraine. – Kharkiv, 2020. This dissertation seeks to explore psycholinguistic avenues of target texts’ linguistic features that destroy the translated language by erasing its natural pattern and by adding there a bundle of alien features causing its lexical, syntactical, and stylistic deficiencies. These destructive features, or “deforming tendencies”, are traditionally treated in translation studies as “translation universals”, “shifts”, “laws”. Thus, the study aims to find out psycholinguistic regularities of English-Ukrainian literary translation as compared to the source texts, i.e. S-regularities, and psycholinguistic regularities of literary translation by comparing Ukrainian translations with non-translations in this target language, i.e. T-regularities. Literary translation is a multifaceted psycholinguistic process of the translator’s psycho- semiotic reproduction of the source text by means of the target language. The effect of this process is the creation of a cognitively asymmetrical new text retaining conceptual information, although containing deformations of syntactical, stylistic, and pragmatic features of the original. Relevance Theory employed in the research explains a conceptual-procedural distinction as a major distinction made between two types of linguistically encoded information. Conceptual information expressed by content words is treated as encoding concepts whereas words with procedural meaning contribute to the derivation of implicatures, certain ways of processing propositions. Psycholinguistic regularities of translation, therefore, are viewed as a result of the subliminal translation-inherent processes that can be traced in the use of function words encoding procedural meaning. Consequently, two ways of the input information processing – implicit/ automatic based on probabilistic principle of parallel-distributed activation, and explicit (arbitrary) principle based on local serial processing with the help of metalinguistic and pragmatic knowledge – are singled out
Keywords: зіставний корпус; паралельний корпус; перекладна закономірність; процедурне значення; психолінгвістика; LIWC; translation regularity; parallel corpus; comparable corpus; procedural meaning; psycholinguistics